2017
DOI: 10.1039/c7ra09868e
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient gas-dominated and water-resistant flame retardant for non-charring polypropylene

Abstract: Traditional phosphorus-nitrogen (P-N) flame-retardant systems for polypropylene (PP) always act through joint action of the gaseous phase and condensed phase, and are accompanied with a decrease of the thermal stability and water resistance. In this work, a novel mono-component and gas-dominated flame retardant, named DPPIP, was prepared through an amidation reaction of diphenylphosphinyl chloride and piperazine, and used to flame retard PP. Experimental results confirmed that both the thermal stability and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…With further increasing the content of PaArg, the PP/PaArg 22 , PP/PaArg 25 , and PP/PaArg 30 samples may achieve the UL-94 V-0 rating and their LOI values further increase to 26.0, 27.0, and 28.5%, respectively. Clearly, PaArg has an excellent flame retarding effect on PP, and its efficiency is also superior to most of traditional typical halogen-free flame retardants such as DPPIP, PETBP, and so forth. For PaLys-filled PP, when the content of PaLys increases to 25 wt %, PP/PaLys 25 may pass the UL-94 V-0 rating. In the vertical burning test, PaLys shows a lower flame-retardant efficiency than PaArg, but it still has a higher flame-retardant efficiency than some traditional flame retardants such as MAPP and ethanolamine–APP .…”
Section: Resultsmentioning
confidence: 99%
“…With further increasing the content of PaArg, the PP/PaArg 22 , PP/PaArg 25 , and PP/PaArg 30 samples may achieve the UL-94 V-0 rating and their LOI values further increase to 26.0, 27.0, and 28.5%, respectively. Clearly, PaArg has an excellent flame retarding effect on PP, and its efficiency is also superior to most of traditional typical halogen-free flame retardants such as DPPIP, PETBP, and so forth. For PaLys-filled PP, when the content of PaLys increases to 25 wt %, PP/PaLys 25 may pass the UL-94 V-0 rating. In the vertical burning test, PaLys shows a lower flame-retardant efficiency than PaArg, but it still has a higher flame-retardant efficiency than some traditional flame retardants such as MAPP and ethanolamine–APP .…”
Section: Resultsmentioning
confidence: 99%
“…Symbols are indicative of different types of nitrogen flame retardant used. Here: ■ MP-40 [ 63 ], MPPK-15, MPPK-20, MPPK-25 [ 64 ], MTP-15, MTP-20, MTP-25, MTP-30, m-MTP-30 [ 65 ], MPyP-30 [ 57 ], MPyP-30, TA-CFA-30 [ 66 ], TA-CFA-30 [ 39 ], TA-CFA-30 [ 40 ], TA-CFA-25 [ 37 ], TA-CFA-25 [ 32 ], TA-CA-ZnO-25 [ 29 ], TA-CA-25 [ 67 ], TA-CA-20 [ 27 ], TA-CA-20 [ 23 ], TA-IFR-20 [ 68 ], TA-IFR-25 [ 31 ], PI-FR-25 [ 69 ], PI-IFR-30 [ 70 ], PI-IFR-20, PI-IFR-30, PI-IFR-40 [ 71 ], NOR116-0.5 [ 72 ], NOR116-0.3 [ 73 ], PPU-CA-25 [ 50 ], N-FR-22, N-FR-25 [ 74 ], N-IFR-5, N-IFR-10, N-IFR-15, N-IFR-20, N-IFR-25 [ 75 ], N-IFR-25 [ 76 ], PN-IFR-30 [ 56 ].…”
Section: Figurementioning
confidence: 99%
“…Overall, like what happened to other polymers [77,78], combinatorial flame retardants may be the solution to flammability reduction of PP materials. [65], MPyP-30 [57], MPyP-30, TA-CFA-30 [66], TA-CFA-30 [39], TA-CFA-30 [40], TA-CFA-25 [37], TA-CFA-25 [32], TA-CA-ZnO-25 [29], TA-CA-25 [67], TA-CA-20 [27], TA-CA-20 [23], TA-IFR-20 [68], TA-IFR-25 [31], PI-FR-25 [69], PI-IFR-30 [70], PI-IFR-20, PI-IFR-30, PI-IFR-40 [71], NOR116-0.5 [72], NOR116-0.3 [73], PPU-CA-25 [50], N-FR-22, N-FR-25 [74], N-IFR-5, N-IFR-10, N-IFR-15, N-IFR-20, N-IFR-25 [75], N-IFR-25 [76], PN-IFR-30 [56].…”
Section: Nitrogen-based Flame Retardantsmentioning
confidence: 99%
“…In addition, there is another phosphonate prepared using the reactions between diphenylphosphinic chloride (DPCl) and phenolic hydroxyl groups . It is found that diphenyl phosphinate groups are more likely to function in the gas phase. A flame retardant (DPOD) was derived from DPCl and daidzein and was applied in EP. A UL-94 V-0 level and a LOI of 34.7% were obtained for the composites with 6 wt % DPOD.…”
Section: Introductionmentioning
confidence: 99%